In-situ fabrication of polypyrrole composite with MoO3: An effective interfacial charge transfers and electrode materials for degradation and determination of acetaminophen. (March 2022) - Srinithi, Subburaj; Balakumar, Vellaichamy; Chen, Shen-Ming
Abstract: Pharmaceutical wastes, acetaminophen (AP) widely used in medical fields, is often discharged into water, causing harm to human health. Hence, there is an urgent need to effectively remove AP from wastewater systems. In this paper, polypyrrole (PPy) composite with MoO3 has been synthesized via an in-situ polymerization method. The as-prepared materials were thoroughly characterized by XRD, FT-IR, UV-DRS, SEM, TEM and mapping techniques. The as-prepared MoO3 @PPy composite was utilized to removal of AP via photocatalytic degradation and electrochemical determination. Under optimized composite, MoO3 @PPy (2) showed an excellent photocatalytic degradation and electrochemical determination of AP compared to pure MoO3 and all other composites. The higher catalytic activity was ascribed to the effective interfacial charges transfer, reduce the recombination and enhance the active surface area of electrode via a synergistic effect. The photocatalytic degradation mechanism, rate and kinetic of the reaction were investigated and discussed. The major active degradation species and an effective charge transfer properties were confirmed by trapping experiments and photocurrent spectra. In addition, the MoO3 @PPy (2) modified GCE exhibit the AP determination activity by DPV with a linear range of 0.05–546 μM. The limit of detection and sensitivity of electrode were 0.0007 μM and 0.242 μM −1  cm −2 respectively. Moreover, the proposed electrode showed good selectivity, stability and reproducibility. This method was useful for the determination of AP in real samples. Graphical abstract: Image 1 Highlights: The MoO3 @PPy composites were synthesized via a simple in-situ polymerization method. The MoO3 @PPy composite exhibits good photocatalytic and electrocatalytic performance. The photo- and electro-catalytic mechanism were investigated. The MoO3 @PPy composite modified electrode possess excellent stability and reusability. The modified electrode was utilized for the determination of AP in real samples.